Thermal Evaluation of Biocomposites Made from Poly(Lactic Acid) and Cottonseed Byproducts - Zhongqi He; Sunghyun Nam; Sourabh Kulkarni; Mohammad Bagheri Kashani; Ramaswamy Nagarajan (Macromol)
Poly(lactic acid) (PLA) is derived from sugar-based materials. While it is a leading sustainable biopolymer, PLA has been integrated with other agricultural coproducts (e.g., lignin, protein, and starch) to reduce its cost and enhance its modulus and biodegradability. Cottonseed oil and meal are the byproducts of the cotton fiber industry. In this work, four biocomposites were formulated with PLA, cottonseed oil, washed cottonseed meal, and plasticizing reagent glycerol with different formulation ratios. The thermal degradation behaviors were examined via thermogravimetric (TG) analysis under air and nitrogen conditions with the neat PLA sample as a control. The thermal decomposition characteristic values were impacted by both the biocomposite formulation and the heating rates of 1, 2, 5, and 10 °C min−1. Results from two kinetic modeling methods that were examined indicated that the activation energy was relatively steady for the neat PLA in the whole degradation process. Generally, the low activation energy values of biocomposites other than PLA under nitrogen conditions implied that these cottonseed byproduct constituents promote the thermal decomposition of these biocomposites. However, the presence of oxygen would confound the thermal decomposition of the biocomposites, as shown by variable activation energy curves with higher values under air conditions. TG-FTIR analysis revealed that the major gaseous compounds were carbonyl, carbon dioxide, carbon monoxide, methane, and water, which were derived from the thermal decomposition of the biocomposites.